(untitled) (Patan Prospective Journal, 2024)
This paper encompasses the concept of aristocracy and its significance in current Nepalese politics. How the popular Nepalese politicians and their respective political parties have failed to execute the principles of political science that teaches the process of governance in a polity. This article is based on the secondary data collected from both print and electronic versions. The research has been grounded on critical and analytical approach to look into the political figures who control and affect Nepalese politics. Most of the items of information in this paper have been anecdotal and they hold significance in the contemporary Nepalese politics.